2019
DOI: 10.1177/0018578719851457
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience of a Standalone Robotic Device for Batch Compounding of Small-Volume Parenteral Preparations

Abstract: Purpose: Intravenous (IV) drugs prepared by a robotic device offer additional safeguards and advantages, which result in decreased errors and wastage, operational efficiency, and a retrievable electronic audit trail when compared with the traditional method of IV drug compounding. Objectives: To describe the real-world experience of using Robotic IV Automation (RIVA; ARxIUM) from its implementation phase (August-December 2014) through to its operational phase (March 2015-March 2018) for batch compounding of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Five studies [ 9 , 10 , 25 , 30 , 32 ] evaluated the incidence of preparation failures. The model used in 2 of the studies was the CytoCare, and the incidence of failures was 12% (n = 1028) [ 10 ] and 18.7% (n = 4509), [ 9 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies [ 9 , 10 , 25 , 30 , 32 ] evaluated the incidence of preparation failures. The model used in 2 of the studies was the CytoCare, and the incidence of failures was 12% (n = 1028) [ 10 ] and 18.7% (n = 4509), [ 9 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The model used in another study was the APOTECAChemo, and the incidence of failures was 2.44% (n = 11,642). [ 30 ] A 3-year real-world study [ 25 ] showed that the percentage of actual failed preparations was <1% by RIVA. The reasons for preparation failures included robot shutdowns, mechanical failures, recalibration, and other practical problems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations